Improving the Overall Equipment Effectiveness (OEE) of an automotive sector company by reducing downtime and monitoring the control of supplies needed for preventive maintenance: Improving the OEE: an automotive sector company - Chávez Medina, Juan; Santiesteban López, Norma Angélica; Perez Flores, Isis Vianney (Estudios de Administración, 2021)
The subject automotive company is specialized in the manufacture and development of labels using flexographic printing processes; it looks forward to increasing its profitability in sales in 2025. This research seeks to increase the availability of machinery in the area of flexographic printing by reducing downtime caused by breakdowns and improving and controlling maintenance spares through A3 Reports. The methodological section describes all the activities involved in the implementation of the research, guaranteeing a correct integrated traceability to the specific targets. Cause and effect diagrams, the Pareto diagram and the Five Whys are among the techniques used. We concluded that there was a series of imbalances causing a waste of productive time and affecting the levels of productivity and availability calculated by the OEE.